SMARTphone and social media-based Cardiac Rehabilitation and Secondary Prevention (SMART-CR/SP) for patients with coronary heart disease in China: A randomised controlled trial protocol - Dorje, T.; Zhao, G.; Scheer, A.; Tsokey, L.; Wang, J.; Chen, Y.; Tso, K.; Tan, B.; Ge, J.; Maiorana, Andrew (BM J Group, 2018)
Introduction: The burden of cardiovascular disease (CVD) is rapidly increasing in developing countries, however access to cardiac rehabilitation and secondary prevention (CR/SP) in these countries is limited. Alternative delivery models that are low-cost and easy to access are urgently needed to address this service gap. The objective of this study is to investigate whether a smartphone and social media-based (WeChat) home CR/SP programme can facilitate risk factor monitoring and modification to improve disease self-management and health outcomes in patients with coronary heart disease (CHD), after percutaneous coronary intervention (PCI) therapy. Methods and analysis: We propose a single-blind, randomised controlled trial of 300 patients post-PCI with follow-up over 12 months. The intervention group will receive a smartphone-based and WeChat-based CR/SP programme providing education and support for risk factor monitoring and modification. SMART-CR/SP incorporates core components of modern CR/SP: Physical activity tracking with interactive feedback and goal setting; education modules addressing CHD understanding and self-management; remote blood pressure monitoring and strategies to improve medication adherence. Furthermore, a dedicated data portal and a CR/SP coach will facilitate individualised supervision and counselling. The control group will receive usual care but no formal CR/SP programme. The primary outcome is change in exercise capacity measured by 6 minute walk test distance. Secondary outcomes include knowledge and awareness of CHD, risk factor status, medication adherence, psychological well-being and quality of life, major cardiovascular events, re-hospitalisations and all-cause mortality. To assess the feasibility and patients' acceptance of the intervention, a process evaluation will be performed at the conclusion of the study. Ethics and dissemination: Ethics approval was granted by both the Human Research Ethics Committee of Fudan University Zhongshan Hospital (HREC B2016-058) and Curtin University Human Research Ethics Office (HRE2016-0120). Results will be disseminated via peer-reviewed publications and presentations at conferences. Clinical trial registration number: ChiCTR-INR-16009598; Pre-results.